KARAKTERISASI MORFOLOGI, PERBANYAKAN VEGETATIF DAN POTENSI BAMBU (GIGANTOCHLOA DAN SCHIZOSTACHYUM) SEBAGAI TANAMAN UNTUK KONSERVASI TANAH DAN AIR - Trimanto Trimanto; Desya Wahyu Annisa; Dzaskyah Hanasari (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2020)
The potential of bamboo as a plant for soil and water conservation can be identified by the morphological character. The quality of bamboo can be shown from the morphological character. Bamboo is a plant that is difficult to propagate generatively, while there is a paucity information on the vegetative propagation of bamboo species especially genus of Gigantochloa and Schizostachyum. The aims of this research is to characterize morphology of bamboo, studies of bamboo propagation with vegetative method and measure the potential of bamboo as a plant for soil and water conservation. 4 species of bamboo namely Gigantochloa atroviolaceae Widjaja, G. robusta Kurz., G. luteostriata Widjaja and Schizostachyum zollingeri Steud.are used in this study. The result of morphology characterization show that four species of bamboo have unique morphological characteristics from reed midribs, reed height, diameter, leaves and roots. The results of vegetative propagation of bamboo using different growing media show that the compost + soil (1: 1) is the best for bamboo growth. Soil media can also be used as an alternative media for vegetative propagation. Sand mediagives the lowest growth. G. atroviolaceae and G. robusta are species of bamboo that suitable for soil and water conservation. Both species of bamboo are characterized by strong reed, dense growth and canopy, good quality of litter, and a strong root system that supports to soil and water conservation.